Estudos histopatológicos de mamoplastias redutoras em hospital universitário. Análise de 10 anos - Sugita, Danilo Hideki (2014)
This transversal study intends to verify the frequency of histopathological findings diagnosed in specimens of reductional mammoplasthy performed in ten years; assessing whether there is a statistical difference in this frequency among women younger or older than 35 years; and then contribute to the debate about histopathological examination of all surgical specimens as a routine. The records of patients undergoing reductional mammoplasty between 2002 and 2011 were reviewed to analyze the histopathological reports and distributed into two groups: women younger or older than 35 years. Findings were classified according to the Cancer Committee of the College of American Pathologists, estimating the relative risk of the lesion associate to breast cancer. There were 389 surgeries performed. Histopathological alterations were found in 228 (58,61 %) specimens. Nonproliferative lesions were identified in 208 (53,47 %) patients and proliferative lesions in 12 (3,08%), being the most common papilloma (1,5%). Of the atypical epithelial hyperplasia, found in 7 (1,79%) cases, there were 4 (1,02%) atypical ductal hyperplasia and 4 (1,02%) atypical lobular hyperplasia. Invasive carcinoma (PT1a) was diagnosed in 1 (0,25%) case. Frequency of the findings was higher (p < 0,05) in the older group. The histopathological examination of all specimens is questionable only in patients under 35 years old. The group above 35 years seems to be benefited by this practice due care imposed in monitoring and/or treatment of patients, as a result of the diagnostics performed by this routine. The low incidence of lesions imposes further studies, for definition with more propriety of a protocol.